2017
DOI: 10.4172/2254-609x.100070
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Provision of Women Friendly Care and Associated Factors among Postnatal Mothers at Three Public Hospitals of Jimma Zone, Oromia Region, Ethiopia, 2016

Abstract: Background: Women friendly care is an approach to care giving with the goal of creating an enabling environment at all level to improve women's access to safe motherhood and reproductive health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
2
9
0
1
Order By: Relevance
“…The nding showed that the women-friendly care provision was (61%) [95%CI (55.73-66.04)] in the study area. The nding of this study was in line with a study conducted in Tanzania 63% (16), however, higher than related study conducted in Western (25.2%), Eastern (38.4%) Ethiopia [17,18], and Bahir Dar (57%) (12), but lower than the study conducted in Jimma (71%), Gamo Gofa (79.1%), Harar Hospitals (85%) and Amhara region hospital (88%) [11,19,20,21].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The nding showed that the women-friendly care provision was (61%) [95%CI (55.73-66.04)] in the study area. The nding of this study was in line with a study conducted in Tanzania 63% (16), however, higher than related study conducted in Western (25.2%), Eastern (38.4%) Ethiopia [17,18], and Bahir Dar (57%) (12), but lower than the study conducted in Jimma (71%), Gamo Gofa (79.1%), Harar Hospitals (85%) and Amhara region hospital (88%) [11,19,20,21].…”
Section: Discussionsupporting
confidence: 88%
“…A structured questionnaire which was adapted from different works of literature and consists of 36 questions and 21 veri cation criteria [3,11,15] is used in this study to assess the level of women-friendly care provision. It was made up of four sections, the rst section was used to assess socio-demographic characteristics of the mother with 13 items, the second section was used to assess obstetric characteristics of participants with 13 items, the third section was used to assess facilities services use and providers related characteristics with 10 items, the fourth section was used to measure the level of women-friendly care provision experienced by mothers during facility childbirth with 21 criteria.…”
Section: Data Collection Tool and Data Collection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoir l'occasion de poser des questions était positivement associé à la satisfaction des clients (Mehata S et al 2017 La plupart des patientes (95,7%) étaient satisfaites du coût de leur séjour. Le coût élevé des prestations constitue un facteur d'insatisfaction (Tesfaye R et al 2016, Okonofua F et al 2017, Mehata S et al 2017, Hurissa BF et al 2017). Cependant la qualité des services dans le secteur privé de la santé qui ne reçoit pas de subvention est satisfaisante à cause des commodités et de la prise en charge (Andaleeb SS, 2000).…”
Section: Satisfaitunclassified
“…Continuous support of a woman from her husband increases the satisfaction of the husband and father-baby bonding. 17 However, despite scholars clearly stating the benefits and women's willingness, desire, and/or profound need for companionship during labor, 18 many health care facilities in developing countries still do not promote the practice of companionship during labor and delivery. [19][20][21] Because of this many women in LMICS choose home and TBA than health facilities and SBA respectively to give childbirth, 22,23 more than half of women in Ethiopia still deliver at home.…”
Section: Introductionmentioning
confidence: 99%